Smartphone-Based Portable Bioluminescence Imaging System Enabling Observation at Various Scales from Whole Mouse Body to Organelle - Mitsuru Hattori; Sumito Shirane; Tomoki Matsuda; Kuniaki Nagayama; Takeharu Nagai (Sensors, 2020)
Current smartphones equipped with high-sensitivity and high-resolution sensors in the camera can respond to the needs of low-light imaging, streaming acquisition, targets of various scales, etc. Therefore, a smartphone has great potential as an imaging device even in the scientific field and has already been introduced into biomolecular imaging using fluorescence tags. However, owing to the necessity of an excitation light source, fluorescence methods impair its mobility. Bioluminescence does not require illumination; therefore, imaging with a smartphone camera is compact and requires minimal devices, thus making it suitable for personal and portable imaging devices. Here, we report smartphone-based methods to observe biological targets in various scales using bioluminescence. In particular, we demonstrate, for the first time, that bioluminescence can be observed in an organelle in a single living cell using a smartphone camera by attaching a detachable objective lens. Through capturing color changes with the camera, changes in the amount of target molecules was detected using bioluminescent indicators. The combination of bioluminescence and a mobile phone makes possible a compact imaging system without an external light source and expands the potential of portable devices.